The hunchback of Notre Dame (1939) [videorecording (DVD)] - Dieterle, William, 1893-1972; Laughton, Charles, 1899-1962; Hardwicke, Cedric, 1893-1964; O'Hara, Maureen, 1920-2015; Hugo, Victor, 1802-1885 (Warner Home Video, 2010)
Gypsy Esmerelda and malformed bellringer Quasimodo fall victim to the machinations of church and underworld leaders in medieval Paris.